Effect of Inorganic Fillers on the Friction Properties of Polyamide 66 - Raja, V.L.; Kumaravel, A.; Sundaram, S. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Organic materials are those whichÂ have carbon elements in them and the inorganic materials are those whichÂ do not have carbonÂ elements and those obtained from earth materials such as minerals and the atmosphere.Â The inorganic materials have advantages such as high thermal stability, chemical stability etc.Â Fly ash and silica fume are inorganic industrial wastes which are produced in large quantities during production of power and silicon respectively. These are the sources of land pollution and this pollution could be minimized if they are successfully reused in appropriate applications.Â . The polymer composites are becoming suitable alternative materials for metals in various tribological applications and so wear and friction studies of these materials gain significance. Polyamide 66, also known as Nylon 66 are engineering polymers used in such applications. Nylon was reinforced with these fillers in 5 to 25 % weight fraction increasing in steps of 5%, using a twin- screw extruder. The friction tests were carried out under dry sliding conditions in a pin-on-disc type friction and wear monitoring test rig at different normal loads and at a constant sliding distance and velocity. Friction coefficient of both composites have found to be decreased than pure Nylon. The friction coefficient of fly ash reinforced Nylon is lesser than the silica fume filled nylon at all the tested conditions.